Influence of soil preparation and planting methods on watermelon productivity and quality - Andrade, Reginaldo Almeida; Souza, Fábio Régis de; Nascimento, Luan de Oliveira; Brito, Rychaellen Silva de; Carvalho, Cleverson Agueiro de (Scientia Agraria Paranaensis, 2021)
The productivity and quality of watermelon fruits can be influenced by several factors, edaphic or associated with cultural management, such as, the type and form of soil preparation and planting methods, which can be by direct sowing or through transplanted seedlings. The objective of this work was to evaluate productive characteristics and quality of watermelon fruits grown under different forms of soil preparation and planting methods. The experimental design used was randomized blocks, organized in a 2x3 factorial scheme, containing three replications, with 24 plants per plot. The evaluated factors were two forms of soil preparation and three forms of cultivation. The fruits were harvested when their tendrils showed visible signs of dryness, when their productive and qualitative characteristics were analyzed. The variables analyzed were the number of fruits per plant, fruit mass, transverse and longitudinal circumference of the fruits, total soluble solids (° Brix), total titratable acidity, maturation index (ratio) and total productivity. The planting methods do not alter the productive characteristics and the quality of the watermelon fruits, which proved to be adequate to the standard demanded by the national market. Conventional tillage, with plowing followed by harrowing, increases the number of fruits per plant and total productivity, reaching 30.7 Mg ha-1, a value 35.08% higher than the average for the state of Rondônia and 28.33 % above the national average.